Lung function over the first 3 years of a professional diving career - Skogstad, M. (BMJ Group, 2000)
OBJECTIVES—To characterise diving exposure and pulmonary function in professional divers at the start of their formal education and during the first 3 years of their professional career. METHODS—The study included 87 men at the start of their education as professional divers. At follow up 1 and 3 years after the school 83 and 81 divers respectively were re-examined. Assessment of lung function included dynamic lung volumes and flows and transfer factor for carbon monoxide (Tl(CO)). RESULTS—69 Divers had preschool SCUBA diving experience and had a median number of 70 dives (range 2-3000) to a median maximal depth of 40 (range 10-73) metres. During the 15 week introductory diving course, they had 44 dives (range 38-50) in the depth range 10-50 metres. The median number of dives over the follow up period was 95 (range 0-722) to a maximal median depth of 38 (range 0-98) metres. At the start of the diving course there were no differences in forced vital capacity (FVC), forced expired volume in 1 second (FEV(1)), and in Tl(CO) between the 69 pre-exposed divers and the 18 never exposed divers. The FVC was significantly larger than predicted in both groups. At follow up at 3 years there was a significant reduction in mean (SD) FEV(1) of 1.8% (6.5), in forced mid-expiratory flow rate (FEF(25-75%)) of 6.5% (11.7) and in forced expiratory flow at 75% of FVC expired (FEF(75%)) of 10.4% (16.8). There was no change in FVC. The Tl(CO) was significantly decreased by 4.6% (8.8). No significant effects were found of cumulative diving exposure, including the number of dives, on the relative changes of any of the lung function variables. CONCLUSIONS—The results indicate that divers initially belong to a selected group with large FVC. Exposure to diving may contribute to changes in pulmonary function, mostly affecting small airways conductance.   Keywords: diving; follow up study; pulmonary function